Na’ Pala’ Puyan: An Ethnography of Tax Compliance Based on Dayak Kenyah Customary Values: A Case Study at Pampang Cultural Village - Neta Prismalia; Ibnu Abni Lahaya (FEB Universitas Mulawarman, 2025)
This research aims to understand how the Dayak Kenyah community in Pampang Cultural Village, East Kalimantan, accepts, comprehends, and fulfills tax obliga-tions within their cultural context. This study is motivated by low tax compliance and differences between modern and indigenous tax perspectives. A qualitative method with an ethnographic approach was applied. Data were collected through in-depth interviews, non-participatory observation, and documentation. Inform-ants included customary and village leaders. Data were analyzed using Spradley’s ethnographic model. The findings indicate that the interpretation and implementa-tion of tax are strongly influenced by cultural values. Although tax was initially seen as conflicting with customary law because land is viewed as ancestral herit-age, the community now accepts tax as a state obligation that aligns with custom. A key finding is the customary value of Na’ Pala’ Puyan, which means “to give what is an obligation.” This value serves as the main moral foundation for the community to sincerely fulfill their responsibilities, whether customary, social, or state-related (tax). Compliance is also reinforced by other values such as gotong royong (mutual cooperation), honesty, and responsibility. Customary leaders play a crucial role as intermediaries between the state system and the community. In conclusion, the Dayak Kenyah community’s tax compliance is shaped by a blend of customary values, especially Na’ Pala’ Puyan, moral awareness, social re-sponsibility, and collaboration with the formal state system.